2014
DOI: 10.1073/pnas.1420162111
|View full text |Cite|
|
Sign up to set email alerts
|

Nitric oxide regulates synaptic transmission between spiny projection neurons

Abstract: Significance The function of the basal ganglia relies on striatal spiny projecting neurons (SPNs). Axon collaterals of these GABAergic neurons form connections with other SPNs as a means of a feedback inhibition circuit. The mechanisms that regulate neurotransmission at these local synapses remain poorly understood. In this paper, neurotransmission at SPN collaterals is found to be regulated by the gaseous neurotransmitter nitric oxide, which activates a signal-transduction cascade that transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Taverna et al found that collateral connectivity was profoundly reduced in two mouse models of PD [62], in agreement with work by Flores-Barrera et al [20]. This may result, at least in part, from impaired NO signaling in parkinsonian animals [52]. However, a recent report did not find any significant change in collateral transmission in a genetic model of PD [64].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Taverna et al found that collateral connectivity was profoundly reduced in two mouse models of PD [62], in agreement with work by Flores-Barrera et al [20]. This may result, at least in part, from impaired NO signaling in parkinsonian animals [52]. However, a recent report did not find any significant change in collateral transmission in a genetic model of PD [64].…”
Section: Introductionsupporting
confidence: 69%
“…In PD models, both up-regulation and down-regulation of the NO/cGMP signaling pathway have been reported [5052]. Why there is a discrepancy is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For this mechanism to work, the signaling mechanisms governing LTP induction would have to oppose those of NO-LTD. As Ca 2+ entry through NMDA receptors is necessary for LTP induction in SPNs (Shen et al, 2008), phosphodiesterase 1 – a striatally enriched, Ca 2+ /calmodulin dependent phosphodiesterase that preferentially degrades cGMP – might mediate this interaction (Bender, 2006). An additional possibility may be that NO released from PLTSIs also simultaneously tunes GABAergic inputs within the striatum, specifically from other interneurons onto SPNs, a possibility that has been described elsewhere (Nugent et al, 2007; Sagi et al, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…For instance, GABA can be closely related to the NO-cGMP pathway in that NMDAR and NOS can modulate hippocampal GABAergic inhibition via NO-cGMP signaling (Gasulla and Calvo, 2015). Furthermore, the activation of GABA also inhibits the NO-cGMP signaling pathway (Sagi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%